(3MSf GdeOO aj eYQaI af GdYOOs - (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s ((3eMeO Hf CMeO Hf eMeO GdENejej s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd GdbQBf efaUdkG ShQkG hBjGJ s
(3BNQgG (B:s
(3GdhGh NeSI hYTQhf CdakG hNeSI hKeGfhf (B: (3bGd eDdag aQZJ ef JCdjag aj djdI GdLeYI aj UaQ SfI SHY hSHYeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3bQGAGJ hJLhjO (B21) s
Keywords: (3GdbQGAGJ hGdJLhjOs